2023
DOI: 10.3390/e25040568
|View full text |Cite
|
Sign up to set email alerts
|

Social Depolarization and Diversity of Opinions—Unified ABM Framework

Abstract: Most sociophysics opinion dynamics simulations assume that contacts between agents lead to greater similarity of opinions, and that there is a tendency for agents having similar opinions to group together. These mechanisms result, in many types of models, in significant polarization, understood as separation between groups of agents having conflicting opinions. The addition of inflexible agents (zealots) or mechanisms, which drive conflicting opinions even further apart, only exacerbates these polarizing proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…We assume that in each of the three political groups, each individual has preferences with respect to several key political issues [11,34]. These individual preferences range between extremely left-leaning and extremely right-leaning, but more or less aligned with the positions taken by their respective parties.…”
Section: Method: a Dynamic Mean-field Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that in each of the three political groups, each individual has preferences with respect to several key political issues [11,34]. These individual preferences range between extremely left-leaning and extremely right-leaning, but more or less aligned with the positions taken by their respective parties.…”
Section: Method: a Dynamic Mean-field Modelmentioning
confidence: 99%
“…Although research on depolarization is not recent (e.g., [30,31]), in Ref. [5], it is observed that, with a few exceptions [32][33][34], there are no corresponding definitions, measures, and models for depolarization.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, the phenomenon of political polarization has become an issue of major concern among scholars, pundits, journalists, and politicians [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Indeed, the current polarization of modern societies is often perceived as a direct and immediate threat to the stability of democratic societies.…”
Section: Introductionmentioning
confidence: 99%